Differing alterations of sodium currents in small dorsal root ganglion neurons after ganglion compression and peripheral nerve injury - Song Xue-Jun; Huang Zhi-Jiang (SAGE Publishing, 2008)
Abstract Voltage-gated sodium channels play important roles in modulating dorsal root ganglion (DRG) neuron hyperexcitability and hyperalgesia after peripheral nerve injury or inflammation. We report that chronic compression of DRG (CCD) produces profound effect on tetrodotoxin-resistant (TTX-R) and tetrodotoxin-sensitive (TTX-S) sodium currents, which are different from that by chronic constriction injury (CCI) of the sciatic nerve in small DRG neurons. Whole cell patch-clamp recordings were obtained in vitro from L4 and/or L5 dissociated, small DRG neurons following in vivo DRG compression or nerve injury. The small DRG neurons were classified into slow and fast subtype neurons based on expression of the slow-inactivating TTX-R and fast-inactivating TTX-S Na+ currents. CCD treatment significantly reduced TTX-R and TTX-S current densities in the slow and fast neurons, but CCI selectively reduced the TTX-R and TTX-S current densities in the slow neurons. Changes in half-maximal potential (V1/2) and curve slope (k) of steady-state inactivation of Na+ currents were different in the slow and fast neurons after CCD and CCI treatment. The window current of TTX-R and TTX-S currents in fast neurons were enlarged by CCD and CCI, while only that of TTX-S currents in slow neurons was increased by CCI. The decay rate of TTX-S and both TTX-R and TTX-S currents in fast neurons were reduced by CCD and CCI, respectively. These findings provide a possible sodium channel mechanism underlying CCD-induced DRG neuron hyperexcitability and hyperalgesia and demonstrate a differential effect in the Na+ currents of small DRG neurons after somata compression and peripheral nerve injury. This study also points to a complexity of hyperexcitability mechanisms contributing to CCD and CCI hyperexcitability in small DRG neurons.